My path to ACA's leadership. - Linthicum, Lannette (Corrections Today)
The article offers the author's thoughts about being the 105th president of the American Correctional Association (ACA). She recounts her correctional journey, which started when she was sent to Texas by the U.S. Public Health Service's National Health Service Corps in 1986 for her commitment to serve in a health-professional shortage area. The author cites some of the physician position in the system as well as her involvement in ACA.